Acute Systemic Complications of Convulsive Status Epilepticus—A Systematic Review. Issue 1 (January 2018) - Sutter, Raoul; Dittrich, Tolga; Semmlack, Saskia; Rüegg, Stephan; Marsch, Stephan; Kaplan, Peter W.
Abstract : Objectives: Status epilepticus is a neurologic emergency with high morbidity and mortality requiring neurointensive care and treatment of systemic complications. This systematic review compiles the current literature on acute systemic complications of generalized convulsive status epilepticus in adults and their immediate clinical impact along with recommendations for optimal neurointensive care. Data Sources: We searched PubMed, Medline, Embase, and the Cochrane library for articles published between 1960 and 2016 and reporting on systemic complications of convulsive status epilepticus. Study Selection: All identified studies were screened for eligibility by two independent reviewers. Data Extraction: Key data were extracted using standardized data collection forms. Data Synthesis: Thirty-two of 3, 046 screened articles were included. Acute manifestations and complications reported in association with generalized convulsive status epilepticus can affect all organ systems fueling complex cascades and multiple organ interactions. Most reported complications result from generalized excessive muscle contractions that increase body temperature and serum potassium levels and may interfere with proper and coordinated function of respiratory muscles followed by hypoxia and respiratory acidosis. Increased plasma catecholamines can cause a decay of skeletal muscle cells and cardiac function, including stress cardiomyopathy. Systemic complications are often underestimated or misinterpreted as they may mimic underlying causes of generalized convulsive status epilepticus or treatment-related adverse events. Conclusions: Management of generalized convulsive status epilepticus should center on the administration of antiseizure drugs, treatment of the underlying causes, and the attendant systemic consequences to prevent secondary seizure-related injuries. Heightened awareness, systematic clinical assessment, and diagnostic workup and management based on the proposed algorithm are advocated as they are keys to optimal outcome. Abstract : Supplemental Digital Content is available in the text.